Development of a Tuneable Test Problem Generator for Assembly Sequence Planning and Assembly Line Balancing - M. F. F., Ab Rashid; Hutabarat, Windo; Tiwari, Ashutosh (Institution of Mechanical Engineers, 2012)
Assembly optimisation activities that involve assembly sequence planning and assembly line balancing have been extensively studied because of the importance of optimal assembly efficiency to manufacturing competitiveness. Numerous research works in assembly sequence planning and assembly line balancing mainly focus on developing algorithms to solve problems and to optimise assembly sequence planning and assembly line balancing. However, there is a scarcity in works that focus on developing problems to test these algorithms. In optimisation algorithm development, testing algorithms by a broad range of test problems is crucial to identify their strengths and weaknesses. This article proposes a generator of assembly sequence planning and assembly line balancing test problems with tuneable complexity levels. Experiments confirm that the selected combination of input attributes does control the generated assembly sequence planning and assembly line balancing problem complexity, and also that the generated problems can be used to identify the suitability of a given algorithm to problem types.